Two new species of Nicomache (Polychaeta: Maldanidae) from the Southwest Atlantic - de Assis, José Eriberto; Samiguel, Carmen Alonso; Christoffersen, Martin Lindsey (Zootaxa, 2007)
Two new maldanid polychaetes were collected from the Ponta do Cabo Branco beach, Paraíba, Brazil, and represent the first record of the genus Nicomache for the southwest Atlantic. Nicomache (Nicomache) lanai sp. nov. has 22 setigerous segments, two pre-anal asetigerous segments, a dark beige colour on setigers 4–17, an anteriorly rounded prostomium forming a tall, arched keel, elliptical nuchal grooves that open posteriorly, 4–7 acicular spines on setigers 1–3, and an anal funnel with triangular equal-sized anal cirri, with concave sides. Nicomache (Nicomache) brasiliensis sp. nov. also has 22 setigerous and two pre-anal asetigerous segments, but the entire body is light-pink coloured. The prostomium is rounded anteriorly, but is longer, broadening posteriorly, forming a low, straight subterminal keel. This species has parallel nuchal grooves, with a sharp anterior angle, has only 4–6 acicular spines on setigers 1–3, and an anal funnel with short tapering, equal-sized anal cirri with convex sides.